Incidental Extraspinal Findings at Lumbar Spine Magnetic Resonance Imaging. Issue 18 (15th September 2015) - Semaan, Hassan B.; Bieszczad, Jacob E.; Obri, Tawfik; Aldinger, Paul K.; Bazerbashi, Mohamad F.; Al-Natour, Mohammed S.; Elgafy, Hossein
<x xml:space="preserve">Abstract</x> Study Design. Retrospective study of a consecutive series of patients undergoing lumbar spine magnetic resonance imaging (MRI) for low back pain at a single institution. Objective. To determine the prevalence and nondetection rate of incidental extraspinal findings (IESFs) in adult patients undergoing MRI of the lumbar spine performed for low back pain by using a structured approach. Summary of Background Data. Extraspinal findings are depicted on lumbar spine magnetic resonance image. There is limited evidence concerning their prevalence, importance, how often they are missed by interpreting physician, and how to improve their detection. Methods. Our study was approved by our institutional review board committee, which waived informed consent because it was retrospective. Lumbar spine magnetic resonance images obtained for low back pain at our institution from January 2011 to December 2013 were assessed by 3 readers for IESFs using a structured approach and their results compared with the archived reports. Repeat lumbar spine MRI and cases with a history of trauma were excluded. A total of 3024 lumbar spine magnetic resonance images were included. IESFs were classified according to the organ involved and to the model adopted by the modified CT Colonography Reporting and Data System (C-RADS). Nondetection rates were determined by comparing the results of our structured approach with the archived MRI reports. Results. A total of 859 IESFs were found in 671 of 3024 lumbar spine patients undergoing MRI (22%). A total of 623 out of them (73%) were categorized E2 (clinically unimportant finding), 192 (22%) were categorized E3 (likely unimportant finding), and 44 (5%) were categorized E4 (potentially important finding). A total of 347 of 859 findings were not mentioned in the archived reports for a nondetection rate of 40%. The nondetection rate for E4 category findings was 38.6% (17/44). Conclusion. IESFs on lumbar spine MRI are common with a significant nondetection rate of 40% using a nonstructured approach. Specifically, there was a significant nondetection rate of 38.6% for potentially important (E4) findings. Level of Evidence: 3